2001
DOI: 10.1116/1.1409391
|View full text |Cite
|
Sign up to set email alerts
|

Polymer pattern formation on SiO2 surfaces using surface monolayer initiated polymerization

Abstract: The use of surface monolayer initiated polymerization, in which initiators are chemically bound to a surface, can generate robust barrier polymers for pattern formation in silicon by reactive ion etching. The combination of poly(vinylarenes) and a new surface initiator based upon a phenylazo initiator provides excellent etch resistance and superior performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…A first hint might be the kinetic studies on surface-initiated photopolymerization (SIPP) by Dyer who reported that the increase of the polymer brush thickness with the (irradiation) polymerization time was nonlinear for the SIPP of styrene on AIBN-type functionalized SAMs, leading to the proposal of a complex four-stage growth model. In contrast, Rühe et al as well as our group reported on the SIPP of styrene from structured aromatic SAMs equipped with asymmetric azo-initiators. In both cases, the polymer brush layer increase was found to be a strictly linear function of the irradiation time.…”
Section: Introductionmentioning
confidence: 81%
“…A first hint might be the kinetic studies on surface-initiated photopolymerization (SIPP) by Dyer who reported that the increase of the polymer brush thickness with the (irradiation) polymerization time was nonlinear for the SIPP of styrene on AIBN-type functionalized SAMs, leading to the proposal of a complex four-stage growth model. In contrast, Rühe et al as well as our group reported on the SIPP of styrene from structured aromatic SAMs equipped with asymmetric azo-initiators. In both cases, the polymer brush layer increase was found to be a strictly linear function of the irradiation time.…”
Section: Introductionmentioning
confidence: 81%
“…Later, the same group introduced a more suitable asymmetric azo-functionalized SAM featuring a methylmalonodinitrile and an aryl function with higher adsorption. 37,38 The thickness increase of the brush as a function of irradiation time was found to be linear with final thickness values of up to B400 nm after 24 h continuous UV irradiation.…”
Section: Uv Lithographymentioning
confidence: 93%
“…However, the polymer film thicknesses were limited to ≈21.5 nm as a result of the low extinction coefficient (i.e., low UV absorption and initiator efficiency) of AIBN. In subsequent work, [41,42] the surface-tethered AIBN-initiator was modified to improve UV absorption (and hence initiating efficiency, see entry 2 in Table 1) to give access to more densely grown PS films as thick as 500 nm. Patterned PS films with features as small as 1.5 µm were grown also on gold substrates, using disulfide groups for surface-attachment of the AIBN initiator groups (entry 3 in Table 1).…”
Section: Introductionmentioning
confidence: 99%